Manufacture and structural characterisation of novel resorbable phosphate-glass microspheres for bone repair applications - Patel, Uresha (2017)
The principal focus for the materials developed in this thesis was for orthobiologics applications, particularly tailoring phosphate based glasses for the treatment of bone related disorders such as osteoporosis. The degradation and release of therapeutic ions from resorbable phosphate based glasses in aqueous media can potentially be tuned through compositional control. Optimisation of glass formulations was carried out by investigating the physico-chemical and structural characteristics of glasses in two systems: (i) 40P2O5·(16-x)CaO·20Na2O·24MgO·xSrO, where x is 0, 4, 8, 12 and 16 mol% i.e. multicomponent glasses and (ii) (40-)P2O5·16CaO·20Na2O·24MgO·xTiO2, where x = 3, 5, 7, 10 and 12. Furthermore, this project largely focused on the development and manufacture of phosphate based glasses into both non-porous and porous microsphere forms in the 63-125 µm size range using a novel, scalable, inexpensive production process. The physico-chemical properties of glasses in system (i) assessed the thermal properties, dissolution rates and ion release profiles. A decrease in degradation rate was shown with initial addition of 4 mol% SrO, but further addition of SrO showed no significant change. The ion release profiles complemented this trend. The subtle changes in structure and dissolution rates observed for substitution of Ca with Sr were attributed to their similarities in terms of ionic size and charge. Cytocompatability studies of SrO/CaO substitution revealed no cytotoxic effects when culturing osteoblast-like cells (MG63) onto glass discs. Cell metabolic activity appeared to be greatest for higher Sr containing (Sr12 and Sr16) glasses at later time points. However, no significant difference between glass compositions and DNA and ALP activity was observed. Neutron diffraction, 23Na and 31P NMR and FTIR spectroscopy studies investigated the structural effects of substituting CaO with SrO within the glass system (i). 31P solid‐state NMR results showed similar amounts of Q1 and Q2 units for all of the multicomponent glasses investigated. The M‐O coordinations (M= Mg, Ca, Sr, Na) were determined for binary alkali and alkaline earth metaphosphates using neutron diffraction and broad asymmetric distributions of bond length were observed. Neutron diffraction results for the multicomponent glasses were consistent with a structural model in which the coordination of Ca, Sr and Na was the same as in the binary metaphosphate glass, whereas a definite shift to longer distances (r (Å)) of Mg‐O bonds was observed. Glass system (ii) manufactured invert phosphate glasses with a P2O5 content as low as 28mol%. Increasing Ti content increased functional properties such as thermal parameters and density, which were attributed to greater cross linking of phosphate units by Ti ions. The dissolution and ion release profiles of glasses in system (ii) were significantly reduced in comparison to those in glass system (i). However, the release of pyrophosphate units as degradation by products was achieved. 31P MAS NMR studies suggested Ti ions behaved as a network former at lower concentrations of 3 mol%, and switched to behaving as network modifiers with addition of 5 mol% and above of TiO2. This study also showed successful manufacture of both non-porous and highly porous resorbable phosphate glass microspheres with porosity levels of up to 71%, with a surface area of 0.3443 m2/g and high levels of interconnectivity. Furthermore, the dissolution behaviour of these porous microspheres have shown evidence of the formation of hollow, shell-like precipitation layers. This study demonstrated successful development of phosphate based glass compositions for use in orthopaedic related applications and developed a novel manufacturing process resulting in highly porous microspheres, via a single stage manufacturing process (for the first time), where the spherical morphology lends itself to easy delivery options via a minimally invasive route. Furthermore, the porous microspheres can potentially be combined with other biologi